Memória e narrativa: a história da educação da Administração Popular de Fortaleza (1986 – 1988) - Calixto, Francisco José Silva (2002)
The People’s Administration of Fortaleza (1986–1988) is one of the first experiences of the brazilian left in the sphere of public administration, after military governments in Brazil. The goal of this research about the history of the APF educational policy. In other words sought to understand and analyze the meanings of that administrative experience in the field of education in Fortaleza. The theoretical research on outbreaks used this Education lie on the field of history and history education in the perspective of authors such as Paul Ricouer, Friedrich Nietzsche, Michel Foucault, Paul Giles Deleuze and Michel Weyne, Pollak, who are used as plot concepts/notions, narrative, games, memory disputed and segmented. The methodological tools were the documentary and oral sources, the result of interviews with political figures and consultations with the newspapers of the period. The dissertation is evidence for finding that the APF memory is disputed forces standing left in Fortaleza and to demonstrate that, despite numerous misconceptions, administrative-political educational policy was inspired in the popular and democratic education, being understood in education concept observed by the brazilian educator Paulo Freire, in the direction of increasing political awareness of the popular classes.